Y. M. NEVEROV'S ROLE IN ESTABLISHING THE INSTITUTE OF ORIENTAL LANGUAGES (LAZAREV INSTITUTE) - V. . Avetisyan (Гуманитарные и юридические исследования)
2016 marks the 155th anniversary since the appointment of the former Director of the Stavropol school to the position of the director of the Lazarev Institute of Oriental languages. A humanist, a social activist and a teacher created a coherent system of thinking about learning and education. One ofthe outstanding representatives of his time Y. M. Neverov (1810-1893) made a signiicant contribution to the development of national education of the XIX century. The core of the publication are documentary materials from the funds of Russian state historical library, and previously unpublished archival documents from the collections of the state archive of the Stavropol region, characterizing the activity of Y. M. Neverov at the position of the Director of the Institute.